1983
DOI: 10.1177/014107688307600209
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and the Enuresis Alarm Device

Abstract: The effect on sleep of the wire-mesh element within the `buzzer and pad' enuresis alarm device was studied using healthy adult volunteers in a single or double crossover design. Polygraphic recording revealed a reduction in the number of shifts between sleep stages, and in the time spent in wakefulness, movement and stage 1, on the nights when the mesh was in the bed. This effect may be responsible for preventing some of the enuretic episodes which would otherwise have occurred at such times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…This unexpected finding, the reverse of that proposed within the original hypothesis, correlates with the polygraphic evidence (Sireling and Crisp, 1983) that when the wire meshes are in place, there is less light sleep and it is less disturbed.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This unexpected finding, the reverse of that proposed within the original hypothesis, correlates with the polygraphic evidence (Sireling and Crisp, 1983) that when the wire meshes are in place, there is less light sleep and it is less disturbed.…”
Section: Discussionsupporting
confidence: 66%
“…We report here a systematic study of the effect on nocturnal activity of lying on a pair of wire meshes, our hypothesis being that the motility score for the night would be increased under these conditions. A concurrent polysomnographic study was undertaken and is reported elsewhere (Sireling and Crisp, 1983). It revealed that sleep on the mesh was characterized by fewer sleep-stage shifts especially within light non-REM sleep and also by a reduction in light sleep and wakefulness.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we cannot be confident that the control groups were sufficiently comparable to eliminate bias, and none included an adequate placebo. A reliable estimate of the true size of any treatment effect of continuous positive airways pressure is likely to be obtained only if the control group receives a placebo which adequately controls for any effect on sleep or breathing patterns, or both, which can occur when appliances are used during sleep 71 137. The feasibility of using continuous positive airways pressure machines set at a low, non-therapeutic pressure as a comparable placebo has been shown 138.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning with a bell-and-pad device is effective but may be transient [134,137,138]. Psychotherapy generally is ineffective and indicated only if obvious psychopathology is present [126,131].…”
Section: Enuresismentioning
confidence: 99%